Permafrost thaw affects the chemistry of mountain ponds - N Colombo; M Pettauer; S Brighenti; D Godone; F Salerno; R Balestrini; C A Delconte; E Pintaldi; A Benech; L Paro; M Martin; A Brunier; et al. (Environmental Research Letters, 2025)
Permafrost is warming and thawing due to climate change. Among the related effects, water quality modification has gained increasing attention globally. Nevertheless, the impacts of diffuse permafrost thaw on water chemistry in high-mountain areas remain largely unexplored. Here, we investigated the seasonal and interannual variability of water chemistry of two close-by ponds located in high-elevation catchments (European Alps, NW Italy) with and without permafrost. We analyzed major ions and stable water isotopes (2014–2022; weekly to monthly sampling during the ice-free season) and leveraged ground thermal measurements in a 30-m deep borehole. We also used geochemical modeling to investigate the impacts of permafrost thaw on dominant weathering processes. Despite similar climatic conditions, lithological characteristics, and water sources contribution, we observed higher concentrations and more pronounced seasonal increases of most solutes in the pond located within the permafrost catchment compared to the pond in the permafrost-free catchment. This was particularly evident for sulfate, with mean concentrations approximately four times higher in the permafrost pond. In the permafrost catchment, progressive warming and thawing during the investigation period enhanced sulfide oxidation, likely due to increased exposure of unweathered, sulfide-bearing rock particles. However, enhanced weathering did not lead to acidification and water quality deterioration due to pH buffering capacity provided by dissolving silicates and carbonates. Global warming is expected to further accelerate permafrost thawing and related chemical weathering in transitional permafrost areas. Water quality issues may arise in catchments with poor acid neutralizing potential of rocks.